PENERAPAN KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU DENGAN SISTEM ZONASI PADA TINGKAT SEKOLAH MENENGAH ATAS DI KOTA BATAM - Sinta Klaronika S, Melati; Teovani Lodan, Karol (SCIENTIA JOURNAL, 2023)
This study aims to analyze the implementation of school zoning policies in high schoolPPDB (New Student Acceptance) in Batam city, evaluate their impact on equal distributionof access to education, and identify challenges faced in its implementation. The researchmethod used is a qualitative method with a descriptive approach. The data used in thisstudy were collected from interviews with related parties and collected data from variousreliable sources. The results of the study show that the implementation of the PPDBzoning system in Batam City has had a positive impact in achieving equal access toeducation by prioritizing students from each school zone. However, this research alsoidentified several challenges, such as adaptation to various local conditions and theimportance of active community involvement in implementing this policy. This researchcontributes to understanding the implementation of the PPDB policy with the zoningsystem in Batam City and provides recommendations for policy improvement and furtherdevelopment in order to achieve equal and fair access to education for all students inBatam city